Evaluating the Teaching Skills of Mathematics Faculty Members at Private Universities in The Kurdistan Region of Iraq According to Quality Specifications. - Nedhal Abdul Hafedh Taher (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The aim of this study is to evaluate the professional responsibility skills, knowledge skills, and practical skills of teaching mathematics for faculty members in the private universities in the Kurdistan Region of Iraq, to identify the extent of achieved skills in general, and in each skills area and finally to find out the significant differences in the achievement of teaching skills among skill areas and universities. The researcher used the analytical descriptive method in the collection, classification and processing of the data for this study. Based on the monitoring of many theoretical and empirical studies the researcher prepared a list of the mathematics teaching skills, the list contained 21 teaching skills, the researcher also designed a questionnaire consisted of 21 items allocated on the three dimensions. The validity and reliability of the questionnaire were checked. The questionnaire was implemented from 16/9 to 27/9/2019. The study sample was chosen randomly from private universities in Kurdistan Region. The Statistical Package for Social Sciences (SPSS) was used for the processing of the studies data.